Relationship between Parenting Parenting and Smartphone Use for Elementary School Age Children During the Covid 19 Pandemic - Arif Rachman Putra; Budi Handayani; Didit Darmawan; Eli Retnowati; Ella Anastasya Sinambela; Ernawati Ernawati; Jahroni Jahroni; Misbachul Munir; Rahayu Mardikaningsih; Tri Seno Anjanarko; Utami Puji Lestari (Forum Kerja Sama Penddikan Tinggi (FKPT), 2022)
Elementary school age children will experience very fast development. These developments are in the form of physical development and psychological development. Inappropriate use of smartphones in children will have a negative impact on children. In this case, parenting plays a very important role because the family is the first and foremost educational institution for children. From the family environment, especially parents, children will get a moral foundation, character and personality that will be applied now and in the future. The purpose of this study is to identify the relationship between parenting and smartphone use by involving correlation analysis as a statistical tool. The study was carried out during the Covid-19 pandemic in Balongbendo District in Jeruklegi Village. There were 30 elementary school age children who were observed by interviewing parents and giving questionnaires. Studies show that there is a positive and significant relationship between parental parenting and smartphone use. The family has an important role in the supervision and mental development of the child's personality. With good and proper care and supervision from parents, children will avoid the negative impacts of smartphone use.